Acute Macular Neuroretinopathy in a Patient with Retinal Vascular Tortuosity - Izabella Karska-Basta; Weronika Pociej-Marciak; Bożena Romanowska-Dixon; Barbara Bukowska-Mikos (Case Reports in Ophthalmology, 2021)
We report a rare case of a young woman with acute macular neuroretinopathy (AMN) in the right eye and concomitant retinal vascular tortuosity in both eyes. A 19-years-old woman presented with a sudden loss of central vision in the right eye. Apart from flu-like infection 2 weeks before the onset of symptoms, she reported overall good health. She used oral contraceptive pills. Multimodal imaging techniques including color fundus photography, fundus autofluorescence, infrared reflectance imaging, fluorescein angiography, swept-source optical coherence tomography (SS-OCT), and visual field assessment were used for the diagnosis of AMN as well as disease monitoring during follow-up. At presentation, ophthalmoscopy revealed a reddish parafoveal lesion, while SS-OCT showed hyper-reflectivity in the outer plexiform and outer nuclear layers with a slightly disrupted inner segment/outer segment junction. All these imaging findings indicated AMN, but the interpretation was slightly difficult due to the presence of tortuous retinal arteries in both eyes. During the disease course, functional and morphological recovery was documented at 1- and 6-month follow-up. However, as the abnormal appearance of the retinal vessels did not change, congenital retinal vascular tortuosity was diagnosed. Since the pathogenesis of AMN has not been fully elucidated, there is currently no effective treatment. Numerous studies have emphasized a vascular origin and the key role of ischemia in AMN. Our rare case suggests that congenital tortuosity of the retinal vessels, although constituting a common finding in healthy individuals, may be involved in the pathophysiology of the disease.